What are the barriers and how do we manage them? A review of progress over the last 10 years - Wein, Alan (Canadian Urological Association Journal, 2013)
There are several well-known challenges in the management of overactive bladder (OAB). This brief review discusses four of these: shortcomings of current OAB classification, incomplete understanding of pathophysiology, undertreatment, and managing patient expectations.